(untitled) (European Journal of Pure and Applied Mathematics, 2010)
Two generalizations of the Durbin-Watson Statistic d, for testing that the serial correlation, in a given univariate normal regression model, is zero, to its multivariate counter part, are proposed. In the univariate case the moments of d are obtained in terms of generalized gamma functions. Our methodology is based on the generalized quadratic form central Wishart distribution.